Pengaruh Electronic Word of Mouth (E-WOM) Dan Harga Terhadap Keputusan Pembelian Lip stain TimePhoria Pada Platform Tiktok: The Influence of Electronic Word of Mouth (E-WOM) and Price on TimePhoria Lip Stain Purchase Decisions on the Tiktok Platform - Ariqah Putri Khayyira; Lela Elvira; Maria Lapriska Dian Ela Revita (PT Cakrawarti Empat Proksi, 2026)
This study aims to examine the influence of E-WOM (Electronic Word of Mouth) and Price on Purchase Decisions for TimePhoria lip stain products among TikTok users. TimePhoria is a brand that is widely discussed on TikTok through user reviews and recommendations, and has a variety of prices across various e-commerce platforms. In a competitive cosmetics market, understanding how much E-WOM and price influence purchasing decisions is crucial. A quantitative approach was applied in this study by distributing survey questionnaires to 100 respondents, namely female TikTok users who have experience purchasing TimePhoria brand lip stain products. Respondents were selected using a purposive sampling technique. Data analysis was carried out using multiple linear regression analysis which includes data quality testing, classical assumption tests (normality, multicollinearity, and heteroscedasticity), and hypothesis testing through t-tests, F-tests, and coefficients of determination. The results of the study indicate that partially, E-WOM has a positive and significant effect on purchasing decisions with a calculated t value of 5.452 > t table 1.984 (Sig. 0.000), and Price has a positive and significant effect with a calculated t value of 8.024 > t table 1.984 (Sig. 0.000). Simultaneously, E-WOM and Price also have a significant effect on purchasing decisions with a calculated F value of 113.788 > F table 3.08 (Sig. 0.000), with a contribution of 69.5%. These findings imply that companies need to strengthen their E-WOM strategies and set competitive prices to improve consumer purchasing decisions on digital platforms such as TikTok.